تفسير سورة البقرة تفسيرا مقارنا من الآية 83 إلى الآية 123 - دعاس, حاتم; شتوح, بوبكر; نبهي, محمد (University of Eloued-جامعة الوادي, 2022)
"قمنا في هذا البحث والذي هو بعنوان: ""تفسير الآيات من الآية 83 إلى الآية 123 من سورة البقرة تفسيرا مقارنا""، بدراسة تفسيرية تعتمد على المقارنة بين أقوال المفسرين في الآية الواحدة المختلفة اختلافا ظاهره التعارض، حيث تطرقنا من خلال دراستنا لهذه الآيات إلى تسعة آيات عنيت بالتفسير المقارن، درسنا فيها أقوال المفسرين، بعرض جمل الأقوال في المسألة، وأصحابها، وأدلتهم، ثم المناقشة مع ذكر أسباب الخلاف، وأخيرا ذكر القول الراجح. ومن خلال بحثنا توصلنا إلى عدة نتائج أهمها: أن معظم الآيات التي تناولناها بالدراسة كانت تعتمد على أدلة صحيحة، إما من القرآن، أو الأحاديث النبوية، أو في اللغة، أو آثار ثبت النقل عن أصحابها، كما أن الراجح فيها يكون غالبا باختيار أحد الأقوال أو الجمع بينها. يتعلق التفسير المقارن بالأقوال التي يكون فيها الخلاف معتبرا، ولا يتعلق بالأقوال المتهاوية التي ليس لها أدنى اعتبار. "In this research, entitled "Interpretation of the verses from the verses number 83 to the verses number 123", we have performed an interpretive study based on the different opposite interpreters saying in the one verses. We have addressed through our study to nine verses cares about comparative interpretation, in which, we have studied the interpreters saying about it, so, we have discussed thier arguments, showing the reasons of disagreement, carrying out the most correct saying. We have reached several results from this study: the most important is that the verses we have studied were based on authentic argements, either from the Quran or from the Sunnah, or in language, or antique words that its transmission is proved by their owners. Also, The most correct in it is often concluded by the choice of one of the sayings or a combination of them. The comparative interpretation is related to the statements in which the difference is significant and not related to the equal statements that do not have the slightest consideration.
مذكرة ماستر
Keywords: سورة البقرة - التفسير- أسباب الخلاف; Surah Al-Baqarah-interpretation-reasons for disagreement